PENGARUH FINANCIAL DISTRESS, LEVERAGE, PROFITABILITAS, DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA (Studi Empiris pada Industri perdagangan Retail yang terdaftar di BEI tahun 2016-2018) - alif difa miftakhunnimah (Universitas Gajayana Malang, 2020)
This study aims to examine and analyze the effect of Financial Distress, Leverage, Profitability, and Firm Size on Earnings Management. The population in this study are retail industry companies listed on the Indonesia Stock Exchange in 2016-2018. Sample selection using purposive sampling and there are 22 companies that meet the sample criteria. The method used in this study uses multiple linear regression. The results of this study suggest that Financial Distress has a negative effect on earnings management, leverage and profitability have a positive effect on earnings management, and company size has a negative influence on earnings management.